2012
DOI: 10.1103/physrevb.86.155435
|View full text |Cite
|
Sign up to set email alerts
|

Electronic ground-state properties of strained graphene

Abstract: We consider the effect of the Coulomb interaction in strained graphene using tight-binding approximation together with the Hartree-Fock interactions. The many-body energy dispersion relation, anisotropic Fermi velocity renormalization and charge compressibility in the presence of uniaxial strain are calculated. We show that the quasiparticle quantities are sensitive to homogenous strain and indeed, to its sign. The charge compressibility is enhanced by stretching and suppressed by compressing a graphene sheet.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…This difference arises from compressing and stretching strain in the bottom and top edges respectively and as a result the velocity of quasiparticle in the compressed edge is larger than the one in the stretched edge. 16 In order to clarify this analysis, we thus show in Fig. 3 the site-resolved local density of state of those edge states and our numerical results confirm that the faster moving particle on edges is localized on the compressed edge and the slower one is located on the stretched edge.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…This difference arises from compressing and stretching strain in the bottom and top edges respectively and as a result the velocity of quasiparticle in the compressed edge is larger than the one in the stretched edge. 16 In order to clarify this analysis, we thus show in Fig. 3 the site-resolved local density of state of those edge states and our numerical results confirm that the faster moving particle on edges is localized on the compressed edge and the slower one is located on the stretched edge.…”
Section: Numerical Results and Discussionmentioning
confidence: 70%
“…It is realized that, without a magnetic field, the low-energy Hamiltonian of a uniaxially strained graphene around the shifted Dirac points can be easily described through the generalized Weyl Hamiltonian 3,4,8 , in which the uniaxial strain along a specific direction in the (x, y) plane is accompanied with the modifications in the associated Fermi velocity.…”
Section: Theory and Modelmentioning
confidence: 99%
“…1 (b)) and strain tensors. 8 It has been shown that the uniaxial strain due to the modification of the hopping integrals creates an anisotropic energy dispersion around the new Dirac point which is shifted away from its equilibrium position in undeformed graphene. The position of the new K point is…”
Section: Theory and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to patterning, uniaxial strain has also been used to control the properties of GNR and bulk graphene devices [18][19][20][21][22][23][24][25][26][27][28][29][30]. Strain can intrinsically arise due to lattice mismatch between the graphene device and the substrate onto which it is deposited [31][32][33], or can be directly applied (e.g., the application of uniaxial tensile strain on suspended graphene samples) [34,35].…”
Section: Introductionmentioning
confidence: 99%